Hormonal responses to striking combat sports competition: a systematic review and meta-analysis - Slimani, Maamer; Paravlic, Armin Huso; Chaabene, Helmi; Davis, Philip; Chamari, Karim; Cheour, Foued (Biology of Sport, 2018)
Striking combat sports are challenging, commonly stressing the endocrinological system based on a mixture of body-contact actions and physiological efforts. The aims of this systematic review and metaanalysis were to discuss the hormonal responses related to striking combat sports competitions and to investigate the moderator and mediator variables of the hormonal response-competition/outcome relationship. Three electronic databases (i.e., PubMed, Google Scholar and ScienceDirect) were systematically searched (up to February 2016) followed by a manual search of retrieved papers. The data showed a moderate increase in cortisol (C) (ES = 0.79; 95% CI 0.31–1.28; p = 0.001), an extremely large increase in adrenaline (ES = 4.22; 95% CI 2.62–5.82; p < 0.001), and a very large increase in noradrenaline (ES = 3.40; 95% CI 1.03–5.76; p = 0.005) and human growth hormone (HGH) levels (ES = 3.69; 95% CI 1.96–5.42; p < 0.001) immediately following the combat events, compared to the control condition i.e., “pre-combat”. Furthermore, amateur athletes had a larger increase in C levels compared to highly trained athletes (ES = 2.91 [very large] vs ES = 0.56 [small]), while evening events showed greater alterations in C levels compared to morning events (ES = 1.91[large] vs ES = 0.48 [small]), without significant differences between them (p = 0.26 and p = 0.06, respectively). The present meta-analysis also showed a small, insignificant increase in testosterone (T) (ES = 0.47 [small]; 95% CI -0.45–0.99; p = 0.074) and a decrease in insulin-like growth factor 1 levels (ES = -0.20 [trivial]; 95% CI -0.78–0.37; p = 0.486) immediately following the combat events, compared to the control condition. The type of combat sports practised, participants’ gender, and the nature of competition contests (i.e., official vs simulation) did not moderate the relationship between competition and hormonal response. Additionaly, sub-analysis results showed a significant difference between younger and older athletes (Q = 4.05, p = 0.044), suggesting that after combat, younger individuals (less than 17 years of age) had a small decrease in T levels (ES = -0.58), compared with the moderate increase observed in older individuals (ES = 0.76). In conclusion, irrespective of striking combat sports types, the results showed that both official and simulated bouts are a real stressor of the hormonal system of practitioners. Coaches and applied practitioners should adopt “pre-competitive cognitive/coping strategies” to improve the psychological state that mediates the hormonal changes-competition/outcome relationship of their athletes in order to mitigate athletes’ stress.